2004
DOI: 10.1002/nme.893
|View full text |Cite
|
Sign up to set email alerts
|

A coupling of multi‐zone curved Galerkin BEM with finite elements for independently modelled sub‐domains with non‐matching nodes in elasticity

Abstract: SUMMARYWhen the different parts of a structure are modelled independently by BEM or FEM methods, it is sometimes necessary to put the parts together without remeshing of the nodes along the part interfaces. Frequently the nodes do not match along the interface. In this work, the symmetric Galerkin multi-zone curved boundary element is a fully symmetric formulation and is the method used for the boundary element part. For BEM-FEM coupling it is then necessary to interpolate the tractions in-between the non-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, as an alternative a coupling of an FE shell model with the so-called symmetric Galerkin boundary-element method (SGBEM) may be applied [33]. An extensive review of the developments regarding the SGBEM can be found in the work by Ganguly et al [34,35].…”
Section: Coupling Of Fe and Be Regionsmentioning
confidence: 99%
“…However, as an alternative a coupling of an FE shell model with the so-called symmetric Galerkin boundary-element method (SGBEM) may be applied [33]. An extensive review of the developments regarding the SGBEM can be found in the work by Ganguly et al [34,35].…”
Section: Coupling Of Fe and Be Regionsmentioning
confidence: 99%
“…A symmetric coupling of the BEM and FEM was proposed later by Costabel and Stephan [409] followed by the variationally based coupling procedure between the FEM and an indirect ver sion of the Galerkin BEM developed by Polizzotto and Zito [410]. In many papers, the BEM subdomains, see for instance the work by Haas and Kuhn [411] and by Ganguly, Layton and Balakrishna [412], or the FEM subdomains, e.g., the work by Ganguly, Layton and Balakrishna [413], are handled as equivalent finite or bound ary macro elements, respectively. In recent years, however, the idea of adapting one of the two techniques to the other in a sort of master slave technique with macroelements has been gradually abandoned for a more balanced approach.…”
Section: Fast Methodologiesmentioning
confidence: 99%
“…A non matching node coupling of SGBEM and FEM is devel oped by Ganguly, Layton and Balakrishna [413] in the context of a BE based approach. In fracture mechanics, a coupling approach which preserves the independence of the FE and BE meshes is the so called hybrid surface integral finite element technique, see the works by Keat, Annigeri and Cleary [414], Han and Atluri [415] and Forth and Staroselsky [280].…”
Section: Fast Methodologiesmentioning
confidence: 99%
“…Symmetric Galerkin BEM (SGBEM) schemes applied to DD problems [10,[24][25][26][27][28] and contact problems [29][30][31][32][33] represent a valuable alternative numerical technique as they combine the boundary character of BEM with the symmetrical and energy-based formulation typical for FEM. SGBEM also enables an easy and straightforward coupling with finite element subdomains [34][35][36].…”
Section: Introductionmentioning
confidence: 99%